Over the Horizon : A New Levant - World Bank Group (Washington, DC, 2014)
The report is organized as follows. The report begins by providing an analytical basis for the evaluation of potential bilateral economic complementarities between Jordan, Lebanon, Syria, Iraq, Egypt, Turkey, and the Palestinian Territories (where data is available) in chapter one. The analysis goes beyond the aggregate level in order to examine the scope for regional trade and investment in particular industries or products. Building on an analysis of economic complementarities and trade and investment potentials in the sub-region, chapter two analyzes the economic implications of a deeper regional integration. A CGE model examines four scenarios emphasizing different aspects of trade relations among possible members of a new economic integration zone. Chapter three reviews and compares the trade and investment regimes of the Levant countries with a view to identifying the areas of reforms needed to harmonize their policies in order to improve competitiveness collectively and increase trade and investment flows among them. Chapter four reviews the services sectors and levels of regulatory restrictiveness in the context of efforts at regional and global integration of Levant economies. The chapter identifies existing and potential barriers to integrating services markets of the sample countries within the Levant region, and advances a number of policy recommendations centered on the promotion of closer regulatory ties in services markets and expanded trade in services. Chapter five-eight focus on five sectors for an in-depth analysis (financial services, energy, ICT and air transport, and tourism) discussing how liberalization of services trade under the framework of deeper regional economic integration would help countries take advantage of the regional opportunities, including an overview for trade in services in the sub-region. Chapter nine analyzes barriers to deeper regional integration in the Levant, focusing on non-tariff measures, trade facilitation, and logistics issues, and proposes policies to remove these barriers. Finally, chapter ten reviews the current regional agreements, identifies the weaknesses and proposes recommendations for a possible economic zone in the medium to long term.